Bathymetry Beneath Ice Shelves of Western Dronning Maud Land, East Antarctica, and Implications on Ice Shelf Stability - Eisermann, Hannes; Eagles, Graeme; Ruppel, Antonia; Smith, Emma Clare; Jokat, Wilfried; 1 Alfred‐Wegener‐Institute Bremerhaven Germany; 2 Federal Institute for Geosciences and Natural Resources Hannover Germany (Geophysical Research Letters, 2020)
Antarctica's ice shelves play a key role in stabilizing the ice streams that feed them. Since basal melting largely depends on ice‐ocean interactions, it is vital to attain consistent bathymetry models to estimate water and heat exchange beneath ice shelves. We have constructed bathymetry models beneath the ice shelves of western Dronning Maud Land by inverting airborne gravity data and incorporating seismic, multibeam, and radar depth references. Our models reveal deep glacial troughs beneath the ice shelves and terminal moraines close to the continental shelf breaks, which currently limit the entry of Warm Deep Water from the Southern Ocean. The ice shelves buttress a catchment that comprises an ice volume equivalent to nearly 1 m of eustatic sea level rise, partly susceptible to ocean forcing. Changes in water temperature and thermocline depth may accelerate marine‐based ice sheet drainage and constitute an underestimated contribution to future global sea level rise. Plain Language Summary: The grounded ice sheets of Antarctica are stabilized by floating ice shelves. Any loss in ice shelf mass is matched by an increase in ice sheet drainage, which contributes to rising sea level. The ice shelves of western Dronning Maud Land are currently in balance with an inland ice volume that has the potential to raise global sea level by nearly 1 m. Ice shelves lose most of their mass from their bases when warm water intrudes from the surrounding ocean. The extent to which this occurs depends on the depth and shape of the seafloor beneath the ice shelves. We have modeled water depths beneath the ice shelves of Dronning Maud Land using airborne gravity data and depth measurements from seismic, multibeam, and radar data. Our bathymetric models show deep troughs beneath the ice shelves and shallow sills close to the continental shelf. These sills currently limit water mass exchange with Warm Deep Water from the Southern Ocean and so protect the ice shelves from significant melting at their bases. A changing climate with ...